Answer:
and
![g(x) = x + 2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/h4s6vqxfqhnks75tqmge2bwiqc61trbwyz.png)
Explanation:
Given
![h(x) = 3(x+2)^2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/vnjuaqonxuzn8wujbrho04knbvo6loevvg.png)
![h(x) = (fog)(x)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/frdjj3n062e2j7ya00u1fgkg9wmssq0lps.png)
Required
Find possible expressions for f(x) and g(x)
This can be rewritten as:
![h(x) = f(g(x))](https://img.qammunity.org/2021/formulas/mathematics/middle-school/g153iv10xswhdxvnb9lctjm04qws3th76a.png)
Recall that
![h(x) = 3(x+2)^2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/vnjuaqonxuzn8wujbrho04knbvo6loevvg.png)
So;
![h(x) = f(g(x)) = 3(x+2)^2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/90qaylk7rmai4zxejrt1a9zwx2ifsw66bt.png)
![f(g(x)) = 3(x+2)^2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/y66if4vs54ki76nwznchr882p8dheime30.png)
By comparison, the expression in bracket represents g(x);
Hence;
![g(x) = x + 2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/h4s6vqxfqhnks75tqmge2bwiqc61trbwyz.png)
Replace g(x) with x
![f(x) = 3(x)^2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/1xyhocj4wupsdxjxolon6peycdo6fgqtkc.png)
![f(x) = 3x^2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/wnzfpeszbfpdl4vs5a1sh4t2dn2r28phiu.png)
Hence, the possible expressions of f(x) and g(x) are:
and
![g(x) = x + 2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/h4s6vqxfqhnks75tqmge2bwiqc61trbwyz.png)